Bolalar nutq o‘stirishda so‘zlashuv nutqining ahamiyati: Bolalar nutq o‘stirishda so‘zlashuv nutqining ahamiyati - Usmonova, Umida (Maktabgacha taʼlim jurnali, 2021)
The article discusses the specific, lexical, stylistic features of the speech style, the syntax of this speech, the specific research work on the lexicon of speech, and the tasks to be performed in the future.